The surreptitious survival of the emerging pathogen Staphylococcus lugdunensis within macrophages as an immune evasion strategy. (7th August 2018) - Flannagan, Ronald S.; Watson, David W.; Surewaard, Bas G. J.; Kubes, Paul; Heinrichs, David E.
Abstract: Staphylococcus lugdunensis is a commensal bacterium that can cause serious infection suggesting an ability to circumvent aspects of host immunity. We demonstrate here that macrophages fail to kill ingested S. lugdunensis and the bacteria persist for extended periods, without replicating, within mature LAMP‐1‐positive phagolysosomes. Phagocytosed S. lugdunensis also do not intoxicate host cells in contrast to Staphylococcus aureus . Optimal survival of S. lugdunensis requires O ‐acetylated peptidoglycan because an oatA mutant, which is more sensitive to killing by lysozyme than wild type, survived to a lesser extent in macrophages. In vitro models of macrophage infection reveal that viable intracellular S. lugdunensis bacteria can be made to grow by pharmacologic perturbation of phagosome function or by phagocyte intoxication by S. aureus toxins. Remarkably, replicating S. lugdunensis is not constrained by LAMP‐1 and phosphatidylserine‐positive endomembranes, which is distinct from S. aureus that replicates within phagolysosomes. In vivo, S. lugdunensis can also reside in the murine Kupffer cell where the bacteria persist without replicating and require oatA to resist killing in vivo. The intracellular environment of the macrophage represents a niche where S. lugdunensis can exist while protected from extracellular immune factors and may serve as a reservoir from which these bacteria could disseminate.